A method for determining the penetration curve of nanoparticles in porous media with different coatings
By preparing biological membranes, EPS, and soil minerals on the porous media of quartz sand, build a more real environmental simulation system, and determine the penetration curve and deposition rate of nanoparticles. The impact problem realizes the more accurate laws and mechanisms of nanoparticles.
Patent Information
- Application Number
- CN202210677191.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-06-15
AI Technical Summary
Traditional quartz sand porous medium simulations cannot effectively consider the impact of environmental interfaces such as biofilms and minerals, and cannot truly reflect the migration behavior and influence mechanism of nanoparticles in the soil.
By preparing different coatings on quartz sand porous media, including biofilms, extracellular polymers (EPS), and soil mineral coating, build a more real environmental simulation system, determine the penetration curve of nano particles in different coating media And sedimentary rate.
This method can more truly reflect the migration law and influence mechanism of nanoparticles in the ambient medium, provide more accurate nanoparticles migration parameters, and guide behavior tracking and monitoring in the actual environment.
Smart Images

Figure CN115112535B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental engineering, and in particular to a method for measuring the migration of nanoparticles in a complex environmental medium. Background Art
[0002] With the development of nanotechnology and the extensive use of nanomaterials, the emission of nanoparticles into the environment is also increasing. Solid environmental media such as soil and sediment are the main places where nanoparticles gather, and can further migrate into water bodies or organisms. The migration behavior of nanoparticles in soil and sediment will determine their ultimate environmental fate and ecological risks. Therefore, revealing the migration laws of nanoparticles in porous media such as soil and sediment is crucial for the environmental risk assessment and control of nanomaterials.
[0003] Due to the complex composition and strong heterogeneity of soil, it is difficult to conduct single factor analysis and mechanism study on the migration of substances through field soil. However, porous media such as clean quartz sand have a similar structure to soil and are usually used to simulate the migration and transport process of NPs.
[0004] However, the migration of nanoparticles in porous media is closely related to the surface properties of the media. Compared with real soil media, porous media with smooth surfaces such as quartz sand have significantly reduced retention capacity for nanoparticles. In real soil environments, biofilms and soil minerals are the main factors that determine their surface chemical properties and will greatly affect the migration behavior of nanoparticles in the soil.
[0005] Therefore, the nanoparticle migration parameters obtained by traditional quartz sand porous media simulation do not take into account the influence of environmental interfaces such as biofilms and minerals, and cannot effectively guide the tracking and monitoring of nanoparticle behavior in actual environments. It is urgent to develop simulation research methods that can more realistically reflect the surface properties of soil and explore the influence and mechanism of interfaces such as biofilms and soil minerals on the migration of nanoparticles in soil. Summary of the invention
[0006] Technical problem to be solved: The present invention provides a method for determining the penetration curve of nanoparticles in porous media with different coatings, aiming to more realistically obtain the migration process of nanoparticles in environmental media and its related parameters.
[0007] Technical solution: A method for determining the penetration curve of nanoparticles in porous media with different coatings, comprising the following steps: S1. Screening and processing of porous media materials: quartz sand materials are selected for screening to remove organic matter and impurities therein, and after sterilization, they are placed in a sterile electrolyte solution and sealed for standby use; S2. Preparation of porous media with different coatings: the quartz sand treated in the above step is fully mixed with a biofilm culture solution inoculated and cultured for 24 hours, an extracellular polymer (EPS) solution with a concentration of 1 g / L, and a soil mineral suspension with a concentration of 500 g / L, respectively, and After the steps of cultivation, standing, centrifugation and washing, a quartz sand porous medium containing a biofilm, EPS and a soil mineral coating is prepared; S3. Filling and stabilizing the filling column: the prepared quartz sand porous medium containing a biofilm, EPS and a soil mineral coating and the quartz sand medium treated in step S1 are respectively filled into the column, and the LB culture medium diluted 3 times, 0.1 g / L EPS solution and 5 g / L soil mineral suspension are respectively introduced into the filled column at 0.6 mL / min for 12 h using a peristaltic pump, and then 10 mmol / L The loose materials in the filling column were eluted with KCl electrolyte solution at 4 mL / min for 20 min, thereby obtaining a stable filling column with different coating media; S4. Determination of the porosity of the filling column: the filling column was saturated with deionized water from bottom to top by a peristaltic pump, and the pore volume of the filling column was obtained by calculating the volume of deionized water entering the filling column, and the porosity of the filling column was determined; S5. Determination of the penetration curve: the filling column was first balanced with an electrolyte solution, and then the nanoparticle solution to be tested was passed into the filling column, and finally the filling column was eluted with an electrolyte solution, the effluent was collected at fixed intervals and the concentration of nanoparticles in the effluent was monitored using an ultraviolet spectrophotometer, the volume of the solution passed was used as the horizontal coordinate, and the concentration of nanoparticles in the effluent was used as the horizontal coordinate, and the penetration curve of the nanoparticles in the filling column with different coatings was plotted; S6. Determination of the deposition rate: in order to quantitatively compare the deposition kinetics of the nanoparticles in the different penetration curves obtained, the normalized penetration concentration parameter of the nanoparticle migration was obtained from the platform of the penetration curve, and the deposition rate coefficient (k d ), deposition rate coefficient (k d ) is calculated as: Where v is the flow velocity in m / s, θ is the porosity, L is the length of the porous medium in m, C is the nanoparticle concentration in the effluent sample in mg / L, C0 is the nanoparticle concentration in the inlet water in mg / L, and C / C0 is the normalized breakthrough concentration, which is obtained from the platform of the breakthrough curve.
[0008] In step S1, the screening size of the porous medium is quartz sand of 20-30 mesh, the method for removing organic matter is soaking in a 5% dilute HNO3 solution for 30 minutes, the sterilization method is sterilizing in a high pressure sterilizer at 121°C for 30 minutes, and the electrolyte solution used for storage is a KCl solution with a concentration of 10mM.
[0009] In step S2, the bacterial species used in the preparation of the porous medium of the biofilm coating is Pseudomonas aeruginosa (P.Aeruginosa), the culture medium used is LB culture medium, and the biofilm attachment method is to mix the quartz sand medium with the LB culture medium, inoculate Pseudomonas aeruginosa, and continue to culture in the dark at 37°C and 200rpm in a constant temperature shaking incubator for 24 hours.
[0010] In step S2, the method for extracting bacterial EPS includes: ultrasonically treating the expanded cultured bacteria at 40 kHz for 10 minutes, centrifuging at 5000g and 4°C for 15 minutes, collecting the supernatant and high-speed centrifuging at 12000g and 4°C for 30 minutes, then adding 3 times the pore volume of anhydrous ethanol and standing in a 4°C refrigerator for 3 days, high-speed centrifuging to obtain a crude EPS extract, and dialyzing the precipitate with ultrapure water in a dialysis bag with a molecular weight cutoff of 8000D for 3 days to obtain pure EPS.
[0011] In step S2, the preparation method of the mineral-coated porous medium is: mixing the soil mineral suspension and quartz sand in a constant temperature incubator at 30° C. for 3 days, and repeatedly washing with deionized water to remove loose soil minerals on the surface of the quartz sand after the attachment is completed.
[0012] In step S3, the composition of the LB culture medium is: 10 g / L yeast extract, 10 g / L tryptic peptone, and 10 g / L sodium chloride; the diluted LB culture, EPS solution, and soil mineral suspension are introduced at a flow rate of 0.6 mL / min for 12 h, and the direction of the peristaltic pump is changed regularly. The solution used for elution is 10 mM KCl electrolyte solution, and the elution time is 20 min at 4 mL / min.
[0013] In step S5, the filled column is firstly balanced with an electrolyte solution with 15 times the pore volume (PV), then a nanoparticle suspension with 3.6 times the pore volume is introduced, and finally eluted with an electrolyte solution with 3.6 times the pore volume.
[0014] Beneficial effects: Compared with the pure quartz sand filling column commonly used in the existing methods, the porous medium filling columns with different coatings constructed by the present invention have stronger binding and blocking capabilities for the migration of nanoparticles, and can quickly and accurately determine the penetration curves of nanoparticles in different coating media, thereby being able to more truly and comprehensively reflect the migration laws and influencing mechanisms of nanoparticles in environmental media. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Schematic diagram of the experimental device for measuring the penetration curve of nanoparticles in porous media with different coatings in the present invention, wherein 1-peristaltic pump, 2-valve, 3-filling column, 4-quartz sand, 5-biofilm coating, 6-EPS coating, 7-montmorillonite coating, 8-goethite coating, 9-collector.
[0016] Figure 2 This is the penetration curve of the nanoparticles obtained in Example 1 of the present invention in porous media with different surface coatings. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with specific embodiments and drawings, but is not limited thereto.
[0018] Example 1
[0019] A method for measuring the penetration curve of nanoparticles in porous media with different coatings includes the steps of preparing a nanoparticle solution, preparing different coating media, filling and stabilizing a filling column, and measuring the penetration curve, as follows:
[0020] Zinc oxide nanoparticles (ZnO NPs) with a particle size of 50 nm were selected, 0.1 g of the nanoparticles were accurately weighed and dissolved in 1 L of ultrapure water, and then ultrasonically treated (100 W, 25 kHz, 25° C.) for 30 min to obtain a nanoparticle suspension with a concentration of 100 mg / L.
[0021] High-purity quartz sand (16-30 mesh) was sieved with sieves of different apertures to obtain quartz sand of 20-30 mesh, and soaked in a 5% dilute HNO3 solution for 30 minutes and stirred appropriately to remove organic matter therein. The quartz sand was then cleaned with deionized water, sterilized in an autoclave (121°C) for 30 minutes, and finally placed in a sterile electrolyte solution (10mM KCl) and sealed for later use.
[0022] Pseudomonas aeruginosa (CGMCC 1.50) was activated and inoculated into LB liquid culture medium for expansion culture. Then, the quartz sand prepared in the previous step was placed in LB culture medium and inoculated with 1 mL of cultured Pseudomonas aeruginosa suspension. The culture was dark-cultured in a constant temperature shaking incubator (37°C, 200 rpm) for 24 h to allow the biofilm to evenly adhere to and grow on the surface of the quartz sand, thereby obtaining a quartz sand porous medium containing a biofilm coating.
[0023] The bacteria expanded and cultured in the previous step were sonicated at 40kHz for 10 minutes, and then centrifuged (5000g, 4°C) for 15 minutes to remove the bacteria. The supernatant was collected and centrifuged at high speed (12000g, 4°C) for 30 minutes to remove cell residues. The supernatant was then collected and mixed evenly with 3 times the volume of anhydrous ethanol, placed in a 4°C refrigerator and allowed to stand for 3 days. The bottom precipitate was obtained by high-speed centrifugation, which was the crude extract of extracellular polymers. The precipitate was dialyzed with ultrapure water in a dialysis bag with a molecular weight cutoff of 8000D for 3 days to obtain pure extracellular polymers. Finally, the sterilized quartz sand and the extracted EPS were fully mixed for 24 hours to obtain a quartz sand porous medium containing an extracellular polymer coating.
[0024] Goethite and montmorillonite were respectively prepared into a soil mineral suspension with a concentration of 500 g / L, and then mixed with quartz sand in a constant temperature incubator at 30°C for 3 days. After the attachment was completed, the loose soil minerals on the surface of the quartz sand were repeatedly rinsed with deionized water to obtain a quartz sand porous medium containing goethite and montmorillonite coating.
[0025] like Figure 1 As shown, a customized PVC tube was used as the filling column for migration, and its length and diameter were 13 and 1.4 cm respectively. The upper and lower ends of the filling column were blocked with a 100-mesh filter to prevent the quartz sand from flowing out. The quartz sand containing biofilm, extracellular polymers and mineral coating and pure quartz sand medium were tightly filled into the migration column, respectively. The migration experiment was divided into 5 groups, as follows: Figure 1 As shown in the numbers: 4 quartz sand (control); 5 biofilm coating; 6 EPS coating; 7 montmorillonite coating; 8 goethite coating. The background solution and nanoparticle solution were injected into the corresponding filling column for migration test by peristaltic pump, and each migration column was independently operated in turn by valve control, and the effluent was collected and measured.
[0026] In order to make different coatings adhere better to the quartz sand surface, the diluted LB culture, extracellular polymer solution and soil mineral suspension were respectively introduced into the respective filled columns by peristaltic pumps (0.6 mL / min, 12 h, 37 ° C), and the peristaltic direction was changed at regular intervals to ensure uniform coating adhesion. When the coating adhesion was completed, the loose material in the filled column was eluted with 10 mM KCl electrolyte solution for 20 min (4 mL / min).
[0027] Before all migration experiments, the porosity of the packed column must be measured. The porous media with different coatings are densely packed in the packed column, and then the packed column is slowly saturated with deionized water from bottom to top through a peristaltic pump. The pore volume of the packed column is obtained by calculating the volume of deionized water entering the packed column to determine the porosity of the packed column.
[0028] The filled column was balanced with KCl (10mM, pH = 7) electrolyte solution at 1mL / min for 15 times the pore volume (PV), and 3.6PV of nanoparticle suspension (50mg / L, 10mM KCl, pH = 7) was injected into the filled column at a flow rate of 1mL / min, and finally eluted with 3.6PV of KCl (10mM) electrolyte solution. All effluents were collected every 2mL, and the concentration of nanoparticles in the effluent was monitored using an ultraviolet spectrophotometer. The pore volume of the injected nanoparticle solution and the elution was used as the horizontal axis, and the relative concentration of nanoparticles in the effluent was used as the vertical axis to plot the obtained Figure 2 The penetration curves of nanoparticles in porous media with different coatings are shown. From the penetration curve results, it can be seen that the biofilm coating has a stronger blocking effect on the migration of nanoparticles, the mineral coatings of goethite and montmorillonite have moderate blocking effects, and the EPS coating has relatively little effect on the migration of nanoparticles in saturated porous media.
[0029] In order to quantitatively compare the deposition kinetics of nanoparticles in porous media under different conditions, the deposition rate coefficient (k) was determined using the following formula: d ):
[0030]
[0031] Where v is the flow rate (m / s), θ is the porosity, L is the length of the porous medium (m), C is the concentration of nanoparticles in the effluent sample (mg / L), C0 is the concentration of nanoparticles in the influent (mg / L), and C / C0 is the normalized penetration concentration, which can be obtained from the platform of the penetration curve. According to the penetration curve, the k of zinc oxide nanoparticles in pure quartz sand packed columns, biofilm coated packed columns, EPS coated packed columns, montmorillonite coated packed columns and goethite coated packed columns was calculated. d The values are 0.62, 6.35, 1.03, 2.42 and 2.29 respectively, k d The larger the value, the worse the mobility of the nanoparticles in the packed column. Compared with the control (pure quartz sand packed column), the coated packed column has a stronger binding ability with the nanoparticles. Different coatings inhibit the migration of nanoparticles in saturated porous media to a certain extent, among which the biofilm coating has the strongest inhibitory effect.
Claims
1. A method for determining the penetration curve of nanoparticles in porous media with different coatings, characterized in that: The method comprises the following steps: S1. Screening and processing of porous medium materials: selecting quartz sand materials for screening to remove organic matter and impurities therein, sterilizing the materials and placing them in a sterile electrolyte solution and sealing them for later use; S2. Preparation of porous media with different coatings: The quartz sand treated in the previous step was fully mixed with the biofilm culture solution inoculated and cultured for 24 hours, the extracellular polymer (EPS) solution with a concentration of 1 g / L, and the soil mineral suspension with a concentration of 500 g / L, and after culture, standing, centrifugation, and washing steps, a quartz sand porous medium containing biofilm, EPS and soil mineral coating was prepared; S3. Filling and stabilization of the packed column: The prepared quartz sand porous medium containing biofilm, EPS and soil mineral coating and the quartz sand medium treated in step S1 were filled into the column respectively, and the LB culture medium diluted 3 times, 0.1 g / L EPS solution and 5 g / L soil mineral suspension were respectively passed into the filled column at 0.6 mL / min using a peristaltic pump for 12 hours, and then 10 mmol / L The loose materials in the filling column are eluted with KCl electrolyte solution at 4 mL / min for 20 min, thereby obtaining a stable filling column with different coating media; S4. Determination of the porosity of the filling column: the filling column is saturated with deionized water from bottom to top through a peristaltic pump, and the pore volume of the filling column is obtained by calculating the volume of deionized water entering the filling column to determine the porosity of the filling column; S5. Determination of the penetration curve: first, the filling column is balanced with an electrolyte solution, and then the nanoparticle solution to be tested is passed into the filling column, and finally the filling column is eluted with an electrolyte solution, the effluent is collected at fixed intervals and the concentration of nanoparticles in the effluent is monitored using an ultraviolet spectrophotometer, the volume of the solution passed is used as the horizontal coordinate, and the concentration of nanoparticles in the effluent is used as the horizontal coordinate, and the penetration curve of the nanoparticles in the filling column with different coatings is plotted; S6. Deposition rate determination: In order to quantitatively compare the deposition kinetics of nanoparticles in different penetration curves, the normalized penetration concentration parameter of nanoparticle migration was obtained from the platform of the penetration curve, and the deposition rate coefficient (k) of nanoparticles in different coated porous media was calculated by the formula d ), deposition rate coefficient (k d ) is calculated as: Where v is the flow velocity in m / s, θ is the porosity, L is the length of the porous medium in m, C is the nanoparticle concentration in the effluent sample in mg / L, C0 is the nanoparticle concentration in the inlet water in mg / L, and C / C0 is the normalized breakthrough concentration, which is obtained from the platform of the breakthrough curve.
2. The method for determining the penetration curve of nanoparticles in porous media with different coatings according to claim 1, characterized in that: In the step S1, the screening size of the porous medium is quartz sand of 20-30 mesh, the method for removing organic matter is soaking in a 5% dilute HNO3 solution for 30 minutes, the sterilization method is sterilizing in a high pressure sterilizer at 121°C for 30 minutes, and the electrolyte solution used for storage is a KCl solution with a concentration of 10mM.
3. The method for determining the penetration curve of nanoparticles in porous media with different coatings according to claim 1, characterized in that: In step S2, the bacterial species used in the preparation of the porous medium of the biofilm coating is Pseudomonas aeruginosa (P.Aeruginosa), the culture medium used is LB culture medium, and the biofilm attachment method is to mix the quartz sand medium with the LB culture medium, inoculate Pseudomonas aeruginosa, and continue to culture in the dark at 37°C and 200rpm in a constant temperature shaking incubator for 24 hours.
4. The method for determining the penetration curve of nanoparticles in porous media with different coatings according to claim 1, characterized in that: In the step S2, the extraction method of bacterial EPS includes: ultrasonicating the expanded cultured bacteria at 40kHz for 10 minutes, centrifuging at 5000g and 4°C for 15 minutes, collecting the supernatant and high-speed centrifuging at 12000g and 4°C for 30 minutes, then adding 3 times the pore volume of anhydrous ethanol and standing in a 4°C refrigerator for 3 days, high-speed centrifuging to obtain a crude EPS extract, and dialyzing the precipitate with ultrapure water for 3 days in a dialysis bag with a molecular weight cutoff of 8000D to obtain pure EPS.
5. The method for determining the penetration curve of nanoparticles in porous media with different coatings according to claim 1, characterized in that: In step S2, the preparation method of the mineral-coated porous medium is: mixing the soil mineral suspension and quartz sand in a constant temperature incubator at 30° C. for 3 days, and repeatedly washing with deionized water to remove loose soil minerals on the surface of the quartz sand after the attachment is completed.
6. The method for determining the penetration curve of nanoparticles in porous media with different coatings according to claim 1, characterized in that: In step S3, the composition of the LB culture solution is: 10 g / L yeast extract, 10 g / L tryptic peptone, and 10 g / L sodium chloride; the diluted LB culture, EPS solution, and soil mineral suspension are introduced at a flow rate of 0.6 mL / min for 12 h, and the direction of the peristaltic pump is changed regularly. The solution used for elution is a 10 mM KCl electrolyte solution, and the elution time is 20 min at 4 mL / min.
7. The method for determining the penetration curve of nanoparticles in porous media with different coatings according to claim 1, characterized in that: In step S5, the filled column is firstly balanced with an electrolyte solution with 15 times the pore volume (PV), then a nanoparticle suspension with 3.6 times the pore volume is introduced, and finally eluted with an electrolyte solution with 3.6 times the pore volume.
Citation Information
Patent Citations
Experimental determination method for passing capability of polymer gel grains in porous medium
CN103743657A
Method for promoting dispersion and migration of nano ferroferric oxide
CN110054278A